2022
DOI: 10.1177/10848223221127437
|View full text |Cite
|
Sign up to set email alerts
|

Tele Homecare in Premature Infants’ Post-Discharge Early Follow-Up: A Narrative Review

Abstract: The study was conducted to review, categorize and organize early tele-homecare follow-up research in premature infants based on research type, the focus of tele-homecare, and measured outcomes. This narrative review was conducted in 2021 through international databases, including PubMed, Scopus, ProQuest, and Web of Science databases. Studies selected for this purpose included original articles on premature infants. We reviewed 16 out of 267 identified articles. These studies were analyzed according to general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The safety of infants and their families during digital EDPs has been reported by a few other studies 6,17–19 . However, it should be underlined that families in the current study had the opportunity, in line with what others has reported, to receive an indoor consultation at the unit in case of emergency.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The safety of infants and their families during digital EDPs has been reported by a few other studies 6,17–19 . However, it should be underlined that families in the current study had the opportunity, in line with what others has reported, to receive an indoor consultation at the unit in case of emergency.…”
Section: Discussionsupporting
confidence: 81%
“…The Nordic countries dominate in the reports on use of telehome care. 6 In the Nordic countries, discharge readiness is reported to be mainly based on clinical assessment with varying criteria and post-discharge home visit is implemented to a large degree (59%). Half of the Nordic NICUs (51%) provided telehome care solutions for families with preterm infants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations